ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA PARTAI POLITIK SEBAGAI KORPORASI DALAM TINDAK PIDANA KORUPSI - Yolanda Putri; Mexsasai Indra; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One problem that has received much attention in this reform era is corruption. Corruption costs the poor by distorting funds used for development activities. Since its establishment, the Corruption Eradication Commission (KPK) has ensnared 891 corruptors, as many as 223 others are cadres of political parties. So far, politicians with the status of corruption suspects have always been punished by the court, but there is no reward for the political parties where they take shelter. Whereas political parties benefit from criminal acts that occur. By following the line of thought in corporate crime, political parties should also be charged with corruption. This research uses the typology of normative legal research or so-called doctrinal legal research, which more specifically discusses the principles of law. In this study, researchers used the nature of dextiptive research, because researchers described the Juridical Analysis of Criminal Liability of Political Parties as Corporations in Corruption Crimes. The results of the research is up to now political parties have never been held liable for criminal acts for corruption which involve them, whereas based on the characteristics of the corporate concept in the law on corruption eradication, political parties can be equated with corporations in criminal law. Supreme Court Regulation No. 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations, which is the latest legislation issued to act on political parties as corporations, still has weaknesses, including not explaining the criteria of subjects that can be criminally liable. So as to cause the actions of people in carrying out the duties and authorities in a corporation (political party) it can actually be accounted for personally.Keywords: Accountability - Political Parties – Corporations - Criminal Acts - Corruption